GLOBAL INSIGHTS INTO TPACK: A SYSTEMATIC REVIEW OF DEMOGRAPHICS AND THEMATIC PATTERNS AMONG PRE-SERVICE BIOLOGY TEACHERS - Heru Setiawan (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The study aims to analyze the demographic characteristics and trends related to assessment methods and research themes of TPACK among pre-service biology teachers from 2019 to 2024. This research employs a Systematic Literature Review (SLR). The identification and selection of articles follow the PRISMA protocol, utilizing academic databases such as Scopus and Web of Science. The search strategy incorporates relevant keywords and applies eight inclusion and exclusion criteria, resulting in the review of 23 articles. Data extraction is followed by thematic analysis. The finding reveals that the demographic characteristics of studies on TPACK among pre-service Biology teachers shows a variation within a global context with a concentration in Asia and Europe. The research identifies five major themes: (1) The effectiveness of TPACK-development courses in enhancing TPACK competencies (13%), (2) The role of reflection and self-assessment in TPACK development (22%), (3) The integration of TPACK into lesson planning and challenges in real-world application (39%), (4) The influence of cultural and geographical contexts on TPACK development (9%), and (5) The relationship between personal characteristics and successful TPACK development (17%). These findings provide insights into emerging trends and gaps in TPACK research among pre-service biology teachers.